Diferensiasi Muthola’ah Metode Qiro’ati VI Jilid dan V Jilid untuk Peningkatan Mutu Pembelajaran Al-Qur’an Anak Usia Dini: Studi Kasus di TPQ. Choiry Ikhsan Warung Dowo - Nurul Mufidah; Par Mujianto; Mujab Mashudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to identify the differentiation of the Muthola'ah Qira'ati Volume VI and Volume V methods in improving the quality of Al-Qur'an learning in early childhood at TPQ Choiry Ikhsan Warung Dowo. The Qira'ati method, which teaches reading the Al-Qur'an according to the rules of tajwid and makharijul letters, is used to provide a strong foundation in the ability to read the Al-Qur'an. This research uses a case study approach with qualitative descriptive analysis, utilizing interviews, tests and documentation as data collection techniques. The research results show that the application of the Qira'ati method, both Volume VI and Volume V, succeeded in improving students' Al-Qur'an reading skills, with teachers playing a significant role through classical and individual learning. The improvement in quality can be seen from the results of the students' reading tashih which shows a good value category. This research contributes to strengthening the Al-Qur'an learning model based on the Qira'ati method, which not only emphasizes cognitive aspects, but also affective and psychomotor aspects of students.